Augmented Reality-based Physics Learning Media To Improve Students’ Motivation And Learning Outcomes: A Systematic Literature Review - Sidik, Rizki Muhamad; Wiliyanti, Vandan; Gunawan, Indra (Jurnal Pembelajaran Fisika, 2024)
Physics is widely regarded as one of the most challenging subjects for students due to its abstract concepts and unengaging teaching methods, often resulting in low motivation and poor achievement. To address these challenges, this study systematically examines the impact of Augmented Reality (AR) on enhancing student motivation and learning outcomes in physics education, analyzing 20 articles published between 2019 and 2024 through the Systematic Literature Review (SLR) method, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The findings reveal AR's significant potential to transform physics education by visualizing abstract concepts and creating interactive, engaging learning experiences, addressing limitations in traditional methods. However, barriers such as high device costs, limited infrastructure in underdeveloped areas, inadequate teacher expertise, and a lack of diverse AR content hinder its widespread adoption. Long-term research is recommended to evaluate the sustained impact of AR on learning outcomes and motivation across different educational levels and contexts. By addressing these challenges, AR has the potential to become a transformative tool, making physics education more inclusive, engaging, and impactful while fostering a deeper understanding of complex concepts and improving student motivation and achievement.Keywords: Augmented reality, learning motivation, learning outcomes, physics learning, systematic review.DOI: http://dx.doi.org/10.23960/jpf.v12.n2.202405